An Examination of the Influence of Implicit Theories, Attribution Styles, and Performance Cues on Questionnaire Measures of Leadership. (February 2018) - Martinko, Mark J.; Randolph-Seng, Brandon; Shen, Winny; Brees, Jeremy R.; Mahoney, Kevin T.; Kessler, Stacey R.
We examined the direct and interactive effects of respondents' implicit leadership theories (ILTs), attribution styles, and performance cues on leadership perceptions. After first assessing respondents' implicit leadership theories and attribution styles, the participants were randomly assigned to one of nine performance cue conditions ([leader performance: low vs. average vs. high] × [follower performance: low vs. average vs. high]), observed the same leader's behavior via video, and rated the leader by completing three leadership questionnaires. The results supported the notion that these three components of information have both direct and interactive effects on leadership perceptions as measured by the questionnaires. The three components of information accounted for about 10% of the variance in the three questionnaires. The results contribute to theories of information processing by demonstrating how ILTs, attribution styles, and performance cues interact to predict leadership perceptions. Implications regarding the meaningfulness, construct validity, and utility of leadership scales are discussed.